The growth and production of antimicrobial compounds from Lactobacillus plantarum IIA-1A5 on cheese whey medium - Mutmainna, A.; Arief, I. I.; Budiman, C. (Diponegoro University, 2021)
Plantaricin IIA-1A5 is a bacteriocin produced by Lactobacillus plantarum IIA-1A5 which is isolated from Indonesian beef, and it inhibits activity of Gram negative and positive pathogenic bacteria. However, preparation of the antibacterial agent for further applications or studies is costly due to the usage of a bacterial medium. Therefore, this study was aimed to investigate the feasibility of cheese whey as a growth medium for production of the bacteriocin. The growth curve of Lactobacillus plantarum IIA-1A5 in producing antimicrobial compounds was found to occur in the logarithmic phase with an incubation time of 28 and 32 hours. Purification of plantaricin IIA-1A5 produced peptides with a molecular weight of 9.59 kDa consisting of whey and whey+ (20g/L sucrose, 12.5 g/L tryptone and 7.5 g/L yeast extract); thus, the peptide was grouped as class IIa (<10 kDa) bacteriocin. The protein concentration of plantaricin IIA-1A5 with whey+ (sucrose, tryptone, and yeast extract) treatment and whey treatment was 1883.17 mg/ml and lower than 325.58 mg/ml, respectively. Based on the antimicrobial activity test using a paper disc method, plantaricin IIA-1A5 demonstrated antimicrobial activity against Staphylococcus aureus ATCC 25923; the whey and whey+ treatment yielded 38.02 IU/dL and 321 IU/dL, respectively, while antimicrobial activity against Escherichia coli ATCC 25922 using whey and whey+ treatment yielded 44.85 IU/dL and 172.08 IU/dL, respectively. The effectiveness of the antimicrobial properties of plantaricin IIA-1A5 in the whey medium is proven through the results of this study. In short, the whey is appropriate growth medium for bacteriocin production.